Near‐Bed Sediment Transport During Offshore Bar Migration in Large‐Scale Experiments. Issue 5 (7th May 2022) - Grossmann, Florian; Hurther, David; van der Zanden, Joep; Cáceres, Iván; Sánchez‐Arcilla, Agustín; Alsina, José M.
Abstract: This study presents novel insights into hydrodynamics and sediment fluxes in large‐scale laboratory experiments with bichromatic wave groups on a relatively steep initial beach slope (1:15). An Acoustic Concentration and Velocity Profiler provided detailed information of velocity and sand concentration near the bed from shoaling up to the outer breaking zone including suspended sediment and sheet flow transport. The morphological evolution was characterized by offshore migration of the outer breaker bar. Decomposition of the total net transport revealed a balance of onshore‐directed, short wave‐related and offshore‐directed, current‐related net transport. The short wave‐related transport mainly occurred as bedload over small vertical extents. It was linked to characteristic intrawave sheet flow layer expansions during short wave crests. The current‐related transport rate featured lower maximum flux magnitudes but occurred over larger vertical extents. As a result, it was larger than the short wave‐related transport rate in all but one cross‐shore position, driving the bar's offshore migration. Net flux magnitudes of the infragravity component were comparatively low but played a nonnegligible role for total net transport rate in certain cross‐shore positions. Net infragravity flux profiles sometimes featured opposing directions over the vertical. The fluxes were linked to a standing infragravity wave pattern and to the correlation of the short wave envelope, controlling suspension, with the infragravity wave velocity. Plain Language Summary: Nearshore sandbars are seabed features that protect coastal infrastructure behind many sandy beaches around the world. In response to waves, they change in shape and distance to the beach. To improve understanding of their offshore movement, experiments representing natural conditions in a controlled laboratory setting were done. In this context, the underwater transport of sand was measured. The experiments featured groups of single short waves (less than 2.5 m long), which transported sand in different ways. Single short waves largely transported sand toward the beach, and in a very thin layer close to the seabed. Currents, caused by the short waves and their breaking, largely transported sand away from the beach, and over a much wider layer. Interactions between the single short waves in a group created longer waves. They transported sand partly toward and partly away from the beach. The currents transported sand more effectively than the single short waves, which explains the sandbar's offshore movement. The long waves transported less sand and only became important when transports from currents and short waves canceled each other out. This study provides useful information for better forecasting of sandbar movement, improving coastal protection. Key Points: Bar offshore migration resulted from balance of offshore‐directed, current‐related and onshore‐directed, short wave‐related transports Short wave‐ (current‐) related transport dominant in sheet flow (suspended) layer. As they oppose, infragravity transport non‐negligible The presence/absence of time‐lags between concentration and hydrodynamics in the suspended/sheet flow layers affects transport direction